Phosphorus excess changes rock phosphate solubilization level and bacterial community mediating phosphorus fractions mobilization during composting. (October 2021) - Zhan, Yabin; Zhang, Zeyu; Ma, Tiantian; Zhang, Xinjun; Wang, Ruihong; Liu, Yongdi; Sun, Baoru; Xu, Ting; Ding, Guochun; Wei, Yuquan; Li, Ji
Graphical abstract: Highlights: Adding 10% or 15% rock phosphate increased compost maturity and available P. High Olsen P due to rock phosphate addition decreased bacterial diversity. Phosphate-solubilizing ratio is negatively related to C:P and higher as 10% addition. Low C:P ratio (<300, especially 135–160) increased rock phosphate solubilization. Abstract: This study investigated the changes of phosphorus (P) fractions, bacterial community and their response to available P or carbon (C):P during composting with different rock phosphate (RP) addition levels. Results showed that adding RP at 10% or 15% promoted the rise of temperature, maturity and Olsen P accumulation in composting, which had a higher amount of RP solubilization than other groups. Available P changed bacterial composition and decreased diversity in composts. RP solubilization efficiency was negatively correlated to C:P ratio and the highest (22.7%) when 10% RP was added, in which bacterial community changed from "function redundancy" to "intensive P-solubilization". Low C:P ratio (〈300) increased the RP solubilization ratio especially within 135–160. Therefore, this study proposed that adding P-rich substrates to decrease C:P ratio could regulate P-solubilizers' activity for increasing RP solubilization efficiency during composting.